A Quantitative Study on the Benefit of Various Waste Classifications. (27th May 2021) - Zhang, Jiahe; Zhang, Zhenying; Zhang, Jiayue; Fan, Guoyang; Wu, Dazhi
Abstract : Chinese economic development has continuously increased national municipal solid waste (MSW) output. However, the existing MSW classification method is insufficient and exacerbates several urgent problems. There are many factors to consider in Chinese waste classification (population, MSW production, food waste content, water content, economy, environment, and waste disposal methods). Based on research and analysis, MSW classification should highlight and implement treatment methods that focus on incineration, the distinct treatment of kitchen waste, and landfills as a waste disposal supplement. MSW is divided into five categories: kitchen waste, incineration, recyclable, hazardous waste, and other waste. Using economic benefit analysis, life cycle assessment, and radar chart analysis, a quantitative study is conducted on the classification methods of MSW used in Germany, the US, the UK, Sweden, Japan, China, and this study. The results indicate that a more refined classification can effectively improve many aspects of MSW management, especially regarding economic and environmental benefits, which are significantly affected. Effective MSW management can reduce the cost of waste disposal by 69.4% and greenhouse gas and acidic substance emissions and increase the energy utilisation rate four fold. This research is of great significance to environmental protection and the development of a circular economy and provides a reference for the management of MSW.